(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English The period of 1997-1998 was a crucial time for our country. Indonesia was hit strongly by monetary crisis. Indonesia’s production and prices and much of the industrial Asia collapsed. Many industries in Indonesia depending on imported raw material went on bankrupcy. One of these industries was poultry industry. At this time (1997-1998) the eggs and meats production decreased steadily. This paper presents a clear, accurate and interesting picture of the poultry industry structure. It was founded that the major efficient sources covered by poultry industries were feed industries, breeding farms and small scale of the poultry farms. The main conclusion is that an increase in the size of the feed industry unit lead to an increase in the inequality of income distribution. The main solution of establishing the poultry industry is to remove regulatory or other constraints to competitiveness and encourages small farms to enter the established arenas. ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Indonesian Tahun 1997-1998 merupakan periode yang krusial bagi negara kita. badai krisis moneter telah memporakporandakan perekonomian Indonesia. Produksi dan harga-harga baik di Indonesia serta industri di negara-negara Asia lainnya tidak dapat berkutik lagi. Banyak industri yang tergantung kepada bahan baku impor menjadi bangkrut. Salah satu dari industri ini adalah industri peternakan unggas. Saat ini (1997-1998), produksi telur dan daging terus menurun. Makalah ini menggambarkan struktur industri perunggasan secara jelas, teliti dan menarik. Di dapatkan bahwa sumber-sumber ketidakefisienan yang utama di dalam industri unggas adalah industri makanan ternak, pembibitan, dan skala usaha ternak . Kesimpulan utama adalah peningkatan skala usaha industri makanan ternak akan membawa peningkatan ketidakmerataan distribusi pendapatan. Pemecahan masalah yang utama dalam mendirikan industri perunggasan yang mapan adalah dengan menghilangkan peraturan-peraturan atau hambatan-hambatan lainnya dalam meningkatkan daya saing dan mendorong peternak skala kecil ke dalam arena yang sudah mapan